Analisis Harga Saham dan Rata-Rata Abnormal Return Sebelum dan Sesudah Ex-Dividend Date (Studi pada Emiten Indeks Kompas-100) - Hidayati, Alvin Mulya (TRIKONOMIKA, 2014)
The research is aimed at finding out the stock prices before and after the disclosure of dividend distribution and the difference in abnormal return before and after the disclosure of dividend distribution. The research object is companies consistent in the Index Kompas-100 from February 2009 to January 2014. The type of this research is comparative descriptive. The sample used is 54 issuers obtained by conducting purposive sampling. The research periods are 31 days consisting of 15 days before the disclosure of dividend distribution, 1 day at the disclosure of dividend distribution, and 15 days after the disclosure of dividend distribution. This research uses market adjusted model to obtain the value of expected return. While paired sample t-test is used in hypothesis testing. The result of this research shows that there is no significant difference in stock prices as well as in average abnormal return between 15 days before the disclosure of dividend distribution and 15 days after the disclosure of dividend distribution.